STUDNETS’ ABILITY IN USING RELATIVE PRONOUNS; A CASE STUDY AT THE SECOND GRADE STUDENTS OF MTs. DARRUL MUHIBBIN PRAYA - Terasne, Terasne (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study is aimed to find out the students’ ability in using relative pronouns at the Second Grade Students of MTs. Darrul Muhibbin Praya. The samples of this study were classes II-A and II-B consisted of 60 students where each class consist of 30 students. The sample on this study was treated in answering the test grammar test about relative pronouns. The in the form of multiple choice consisted of 50 items and for each item by 2 times. Their ability was proving by finding out the percentage of their test. This particular inference were bravely taken under the “d”(total amount) identification which indicates that the students have ability in using relative pronouns, where “d” valued was 70%, this percentage was significance since obtained from the score 3656 that divided from 60 students. This show that the second grade students of MTs. Darrul Muhibbin Praya were able in using relative pronouns such as (who, whom, whose, which and that)